2013
DOI: 10.1590/s1984-82502013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and stability of valsartan in a solid pharmaceutical formulation

Abstract: Valsartan (VAL) is a highly selective blocker of the angiotensin II receptor that has been widely used in the treatment of hypertension. Active pharmaceutical ingredient compatibility with excipients (crospovidone, hypromellose, magnesium stearate, microcrystalline cellulose and titanium dioxide) is usually evaluated in solid pharmaceutical development. Compatibility and stability can be evaluated by liquid chromatography. Studies were performed using binary mixtures of 1:1 (w/w) VAL/excipient; samples were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Increase in the glass transition temperature may potentially be a sign of increased stability [17][18][19][20][21][22]. In this case, valsartan may be incorporated as molecular dispersion in a glassy polylactide matrix, stabilized by physical separation of the molecules inside the polymer chains [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in the glass transition temperature may potentially be a sign of increased stability [17][18][19][20][21][22]. In this case, valsartan may be incorporated as molecular dispersion in a glassy polylactide matrix, stabilized by physical separation of the molecules inside the polymer chains [46].…”
Section: Resultsmentioning
confidence: 99%
“…Standalone amorphous APIs are rather not used in formulation development. In most cases, amorphous APIs are formulated with excipients in order to, amongst others, provide adequate absorption and to improve their stability [17][18][19][20].…”
Section: (I)mentioning
confidence: 99%
“…Studying the drug-excipient compatibility during the formulation of products is an important process to know any physical and chemical interaction between the compounds. Thermal techniques have been increasingly used for evaluating possible incompatibility quickly through comparison of thermal curves of pure substances with curve obtained from a 1:1 mixture [6]. The characterization of solid-state properties at an early stage by using appropriate analytical methodologies is an essential pre-requisite in the development of solid dosage forms both from scientific and regulatory points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Valsartan (VAL) is a potent and highly selective oral drug largely used for the treatment of hypertension due to its effect as an active antagonist at the angiotensin II AT1-receptor (Krishanaiah et al, 2010) and because its solid-state characterization and compatibility have been established (Julio et al, 2013). In the present study, we report on false Valsartan stability results observed in a degradation study under acid stress condition using HPLC-PDA and the actual instability obtained by HPLC-MS monitoring.…”
Section: Introductionmentioning
confidence: 99%